Preparation method of titanium lithium ion sieve type adsorbent with high adsorption performance
By optimizing the preparation process of titanium-based adsorbents, including mixing lithium sources and titanium compounds, introducing carbon-containing complexing agents, and optimizing calcination and elution treatment, the problems of low adsorption rate and low crystallization degree of titanium-based adsorbents are solved, and high adsorption performance and stability are achieved.
Patent Information
- Application Number
- CN202411816238.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
AI Technical Summary
Titanium-based adsorbents have low adsorption rate and long adsorption equilibrium time, which affects their industrial application. At the same time, the degree of crystallization is not high, resulting in unsatisfactory adsorption performance.
By mixing the lithium source and titanium compound with anhydrous ethanol, slowly dropping in and stirring, introducing a carbon-containing complexing agent, and performing optimized calcination and elution treatment, a titanium-based lithium-ion sieve type adsorbent with high adsorption performance was prepared.
The adsorption capacity is improved, the cycle stability is enhanced, the adsorption equilibrium time is shortened, the titanium is dissolved and loss rate is improved, and an adsorption rate is obtained with high crystallization, small particles and uniform adsorbent.
Smart Images

Figure CN119771336A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ion sieve adsorption materials, and in particular to a method for preparing a titanium-based lithium ion sieve adsorbent with high adsorption performance. Background Art
[0002] As an important strategic resource, lithium is widely used in fields such as medicine, ceramics, and batteries. With the rapid development of the new energy industry, lithium consumption is increasing, which in turn has significantly increased global demand for lithium resources. Therefore, it is imperative to find more efficient and stable lithium extraction technologies. Most of the proven lithium resources are distributed in salt lake brines. Compared with other salt lake lithium extraction technologies such as extraction, electrodialysis, and membrane separation, adsorption has become a commonly used lithium extraction method due to its high adsorption capacity, simple process, low cost, green and efficient, and suitability for high magnesium-to-lithium ratios. Compared with aluminum and manganese adsorbents, titanium adsorbents have attracted much attention due to their high adsorption capacity and strong cyclic stability.
[0003] However, titanium-based adsorbents suffer from low adsorption rates and long equilibrium times, severely hindering their industrial application. Furthermore, some titanium-based adsorbents lack high crystallinity, resulting in suboptimal adsorption performance, such as dissolution rate. Therefore, further improving the adsorption performance of titanium-based lithium ion adsorbents is a pressing technical challenge. Summary of the Invention
[0004] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a method for preparing a titanium-based lithium ion sieve adsorbent with high adsorption performance, so as to solve the problems of unsatisfactory crystallization degree, low adsorption rate and long adsorption equilibrium time of titanium-based adsorbents, thereby increasing the adsorption sites, improving the adsorption capacity, enhancing the cycle stability, shortening the adsorption equilibrium time and reducing the dissolution loss.
[0005] According to the present invention, a method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance comprises:
[0006] S1. Mixing a lithium source and a titanium compound with anhydrous ethanol to obtain solution A and solution B respectively;
[0007] S2. Slowly add solution A to solution B and stir to obtain a mixed solution C;
[0008] S3, dissolving the carbon-containing complexing agent in anhydrous ethanol to obtain a solution D;
[0009] S4, dropping the mixed solution D into the solution C, drying, and then calcining to obtain a lithium ion sieve precursor;
[0010] S5. Elute the lithium ion sieve precursor to obtain a titanium-based lithium ion sieve adsorbent with high adsorption performance.
[0011] Preferably, the calcination treatment includes: calcination at 300° C. to 350° C. for 3.5 hours to 4.5 hours, and then calcination at 780° C. to 850° C. for 11 hours to 13 hours under a N 2 atmosphere.
[0012] Further preferably, the calcination treatment includes: calcination at 330° C. for 4 h, and then calcination at 800° C. for 12 h under N 2 atmosphere.
[0013] Oxygen roasting can remove most of the crystal water, a small amount of organic matter and most of the activated carbon. High-temperature inert gas roasting is to obtain the required Li4Ti5O by reaction at high temperature. 12 Precursor.
[0014] Preferably, in step S1, the molar ratio of lithium to titanium is 4 to 4.5:5; and in step S3, the molar ratio of the carbon-containing complexing agent to titanium is 1 to 1.5:5.
[0015] More preferably, the ratio (molar ratio) of the lithium source, titanium compound and carbon-containing complex is lithium source: titanium compound: carbon-containing complexing agent = 4.1:5:1.25.
[0016] Preferably, the lithium source is selected from one or more of anhydrous or hydrated lithium acetate, anhydrous or hydrated lithium carbonate, anhydrous or hydrated lithium nitrate, anhydrous or hydrated lithium hydroxide, anhydrous or hydrated lithium sulfate, and anhydrous or hydrated lithium chloride.
[0017] Preferably, the elution treatment is acid washing at 20°C to 75°C for 45h to 75h.
[0018] More preferably, the elution treatment is acid washing at 60°C for 72 hours.
[0019] Preferably, the acid solution used in the elution treatment is one or more of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.
[0020] More preferably, 0.15 mol / L hydrochloric acid is used for pickling in the elution treatment.
[0021] Preferably, the lithium ion sieve precursor is Li4Ti5O 12 Precursor.
[0022] Preferably, the high adsorption performance titanium series lithium ion sieve type adsorbent is H4Ti5O 12 Adsorbent.
[0023] Preferably, the temperature of the high adsorption performance titanium-based lithium ion sieve-type adsorbent when adsorbing the lithium-containing solution is controlled at 20° C. to 75° C.
[0024] Preferably, in step S3, the carbon-containing complexing agent is selected from one of citric acid, malic acid, tartaric acid and oxalic acid.
[0025] Further preferably, in step S3, the carbon-containing complexing agent is selected from citric acid.
[0026] The beneficial effects of the present invention are:
[0027] The present invention provides a method for preparing a titanium-based lithium ion sieving adsorbent with high adsorption performance. The preparation method of the present invention has the characteristics of simple process, low cost, and environmental protection. During the preparation process, a titanium-based lithium ion sieving adsorbent with high crystallinity and small and uniform particles can be obtained. By reacting a lithium source with a titanium compound, introducing a carbon-containing complexing agent into the reaction, and optimizing the conditions of the roasting and elution treatments, the dissolution rate of titanium can be reduced, the adsorption surface area can be expanded, thereby increasing adsorption sites, improving adsorption capacity, enhancing cyclic stability and adsorption rate, and shortening adsorption equilibrium time. The method has high practical value in the field of adsorption methods for lithium extraction technology in typical complex multi-ion interactive systems represented by salt lake brine. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 1 is an XRD pattern of the titanium-based adsorbent precursors prepared in Examples 1, 2, 3, and 4 of the present invention and Comparative Examples 1 and 2; Figure 1 In the figure, the horizontal axis represents the diffraction angle (2θ), and the vertical axis represents the diffraction intensity (Intensity);
[0029] Figure 2 is a SEM image of the titanium-based adsorbent precursor prepared in Example 1 of the present invention;
[0030] Figure 3 1 is a graph showing the change in adsorption capacity of the titanium-based adsorbents prepared in Examples 1, 2, 3, and 4 of the present invention and Comparative Examples 1 and 2 over time; Figure 3 In the figure, the horizontal axis represents time (Time), and the vertical axis represents adsorption capacity (Adsorption capacity). DETAILED DESCRIPTION
[0031] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0032] As used herein, the term "including" and its variations are open terms meaning "including but not limited to". The terms "based on", "according to", etc. mean "based at least in part on", "based at least in part on". The terms "one embodiment" and "an embodiment" mean "at least one embodiment". The term "another embodiment" means "at least one other embodiment". The terms "first", "second", etc. may refer to different or the same objects. Other definitions may be included below, whether explicit or implicit. Unless the context clearly indicates otherwise, the definition of a term is consistent throughout the specification.
[0033] As an example, the titanium compound is C 16 H 36 O4Ti, but the present invention is not limited thereto.
[0034] As an example, the lithium titanium compound precursor is Li4Ti5O 12 Precursor.
[0035] As an example, the high adsorption performance titanium series lithium ion sieve adsorbent is H4Ti5O 12 Adsorbent.
[0036] A method for preparing a titanium-based lithium ion sieving agent with high adsorption performance according to an embodiment of the present invention comprises:
[0037] S1. Mixing a lithium source and a titanium compound with anhydrous ethanol to obtain solution A and solution B respectively;
[0038] S2. Slowly add solution A to solution B and stir to obtain a mixed solution C;
[0039] S3, dissolving the carbon-containing complexing agent in anhydrous ethanol to obtain a solution D;
[0040] S4, dropping the mixed solution D into the solution C, drying, and then calcining to obtain a lithium ion sieve precursor;
[0041] S5. Elute the lithium ion sieve precursor to obtain a titanium-based lithium ion sieve adsorbent with high adsorption performance.
[0042] The following describes a specific embodiment of preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance using the method for preparing a doped titanium-based adsorbent with high adsorption rate according to an embodiment of the present invention.
[0043] Example 1
[0044] In this embodiment, the titanium-based lithium ion sieve adsorbent with high adsorption performance is prepared by the following steps:
[0045] (1) Take 4.888g LiC2H3O2·2H2O and 18.5ml C 16 H 36 O4Ti was dissolved in 30ml and 93ml of anhydrous ethanol, respectively, to prepare two solutions A and B. A was slowly dripped into solution B and stirred continuously at room temperature for 12h to obtain a uniform mixed solution C. 2.615g of citric acid was dissolved in 30ml of ethanol solution to prepare solution D. Solution D was slowly dripped into mixed solution C, stirred continuously at room temperature for 0.5h, and then placed in an 80℃ forced air oven to dry for 48h. After drying, the mixture was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 330℃ / 4h. After calcination, the mixture was taken out and fully ground and placed in a porcelain boat, and calcined in a tube furnace under N2 atmosphere at 800℃ / 12h. After calcination, the mixture was taken out and fully ground to obtain a black adsorbent powder Li4Ti5O 12 Its XRD shows Figure 1 , SEM see Figure 2 .Depend on Figure 1 It can be seen that the structure of the obtained precursor is similar to that of spinel-type Li4Ti5O 12 Standard card consistent. Figure 2 It can be seen that the titanium-based lithium ion sieve precursor Li4Ti5O 12 It has a good spinel structure, high degree of crystallization, and small and uniform particles.
[0046] (2) The above lithium ion sieve precursor Li4Ti5O 12 The spinel titanium adsorbent H4Ti5O was obtained by acid washing with 0.15 mol / L HCl at 60 °C for 72 h, with a titanium dissolution loss of 0.29%. 12 0.25g of adsorbent was placed in 50ml of 600mg / L LiOH solution and adsorbed at 60℃ for 72h. The adsorption data curve is as follows: Figure 3 As shown, the adsorption capacity is about 41.84 mg / L.
[0047] Example 2
[0048] The difference between this embodiment and embodiment 1 is the calcination process, and the rest of the configurations are the same.
[0049] (1) Take 4.888g LiC2H3O2·2H2O and 18.5ml C 16 H 36O4Ti was dissolved in 30ml and 93ml of anhydrous ethanol, respectively, to prepare two solutions A and B. A was slowly dripped into solution B and stirred continuously at room temperature for 12h to obtain a uniform mixed solution C. 2.615g of citric acid was dissolved in 30ml of ethanol solution to prepare solution D. Solution D was slowly dripped into mixed solution C, stirred continuously at room temperature for 0.5h, and then placed in an 80℃ forced air oven to dry for 48h. After drying, it was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 350℃ / 4h. After calcination, it was taken out and fully ground and placed in a porcelain boat, and calcined in a tube furnace under N2 atmosphere at 800℃ / 12h. After calcination, it was taken out and fully ground to obtain a black adsorbent powder Li4Ti5O 12 Its XRD shows Figure 1 ,Depend on Figure 1 It can be seen that the structure of the obtained precursor is similar to that of spinel-type Li4Ti5O 12 Standard cards are consistent.
[0050] (2) The above lithium ion sieve precursor Li4Ti5O 12 The spinel titanium adsorbent H4Ti5O was obtained by acid washing with 0.15 mol / L HCl at 60 °C for 72 h, with a titanium dissolution loss of 0.27%. 12 0.25g of adsorbent was placed in 50ml of 600mg / L LiOH solution and adsorbed at 60℃ for 72h. The adsorption data curve is as follows: Figure 3 As shown, the adsorption capacity is about 36.49 mg / L. Compared with Example 1, the adsorption capacity of the adsorbent prepared under the calcination conditions of 330°C / 4h is better than that of the adsorbent prepared under the calcination conditions of 350°C / 4h.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that the roasting treatment in step (1) is different, and the rest are the same settings.
[0053] (1) Take 4.888g LiC2H3O2·2H2O and 18.5ml C 16 H 36 O4Ti was dissolved in 30ml and 93ml of anhydrous ethanol, respectively, to prepare two solutions A and B. A was slowly dripped into solution B and stirred continuously at room temperature for 12h to obtain a uniform mixed solution C. 2.615g of citric acid was dissolved in 30ml of ethanol solution to prepare solution D. Solution D was slowly dripped into mixed solution C, stirred continuously at room temperature for 0.5h, and then placed in an 80℃ forced air oven to dry for 48h. After drying, it was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 330℃ / 4h. After calcination, it was taken out and fully ground and placed in a porcelain boat, and calcined in a tube furnace at 850℃ / 12h under N2 atmosphere. After calcination, it was taken out and fully ground to obtain a black adsorbent powder Li4Ti5O12 Its XRD shows Figure 1 ,Depend on Figure 1 It can be seen that the structure of the obtained precursor is similar to that of spinel-type Li4Ti5O 12 Standard cards are consistent.
[0054] (2) The above lithium ion sieve precursor Li4Ti5O 12 The spinel titanium adsorbent H4Ti5O was obtained by acid washing with 0.15 mol / L HCl at 60 °C for 72 h, with a titanium dissolution loss of 0.30%. 12 0.25g of adsorbent was placed in 50ml of 600mg / L LiOH solution and adsorbed at 60℃ for 72h. The adsorption data curve is as follows: Figure 3 As shown, the adsorption capacity is about 37.3 mg / L. Compared with Example 1, the adsorption capacity of the adsorbent prepared under the calcination conditions of 800°C / 12h is better than that of the adsorbent prepared under the calcination conditions of 850°C / 12h.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that the temperature of the elution treatment and the temperature of the adsorption are different, and the other settings are the same.
[0057] (1) Take 4.888g LiC2H3O2·2H2O and 18.5ml C 16 H 36 O4Ti was dissolved in 30ml and 93ml of anhydrous ethanol, respectively, to prepare two solutions A and B. A was slowly dripped into solution B and stirred continuously at room temperature for 12h to obtain a uniform mixed solution C. 2.615g of citric acid was dissolved in 30ml of ethanol solution to prepare solution D. Solution D was slowly dripped into mixed solution C, stirred continuously at room temperature for 0.5h, and then placed in an 80℃ forced air oven to dry for 48h. After drying, the mixture was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 330℃ / 4h. After calcination, the mixture was taken out and fully ground and placed in a porcelain boat, and calcined in a tube furnace under N2 atmosphere at 800℃ / 12h. After calcination, the mixture was taken out and fully ground to obtain a black adsorbent powder Li4Ti5O 12 Its XRD shows Figure 1 ,Depend on Figure 1 It can be seen that the structure of the obtained precursor is similar to that of spinel-type Li4Ti5O 12 Standard cards are consistent.
[0058] (2) The above lithium ion sieve precursor Li4Ti5O 12 The spinel titanium adsorbent H4Ti5O was obtained by acid washing with 0.15 mol / L HCl at 40 °C for 72 h, with a titanium dissolution loss of 1.12%. 120.25g of adsorbent was placed in 50ml of 600mg / L LiOH solution and adsorbed at 40℃ for 72h. The adsorption data curve is as follows: Figure 3 As shown, the adsorption capacity is about 20.12 mg / L. Compared with Example 1, the elution and adsorption conditions of 40°C / 72h reduce the adsorption capacity of the adsorbent and increase the dissolution rate of titanium compared with 60°C / 72h in Example 1.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Examples 1, 2, and 3 is the different calcination treatments, and the rest of the settings are the same.
[0061] (1) Take 4.888g LiC2H3O2·2H2O and 18.5ml C 16 H 36 O4Ti was dissolved in 30ml and 93ml of anhydrous ethanol, respectively, to prepare two solutions A and B. A was slowly dripped into solution B and stirred continuously at room temperature for 12h to obtain a uniform mixed solution C. 2.615g of citric acid was dissolved in 30ml of ethanol solution to prepare solution D. Solution D was slowly dripped into mixed solution C, stirred continuously at room temperature for 0.5h, and then placed in an 80℃ forced air oven to dry for 48h. After drying, the mixture was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 330℃ / 4h. After calcination, the mixture was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 800℃ / 12h. After calcination, the mixture was taken out and fully ground to obtain a white adsorbent powder Li4Ti5O 12 Compared with Example 1, it can be seen that the properties of the synthesized adsorbent are affected without calcination at 800°C / 12h under N2 atmosphere.
[0062] (2) The above lithium ion sieve precursor Li4Ti5O 12 The spinel titanium adsorbent H4Ti5O was obtained by acid washing with 0.15 mol / L HCl at 60 °C for 72 h, with a titanium dissolution loss of 0.66%. 12 0.25g of adsorbent was placed in 50ml of 600mg / L LiOH solution and adsorbed at 60℃ for 72h. The adsorption data curve is as follows: Figure 3 As shown, the adsorption capacity is about 18.32 mg / L. Compared with Example 1, it can be seen that without calcination at 800°C / 12h under N2 atmosphere, the adsorption capacity of the adsorbent is reduced and the dissolution rate of titanium is increased.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 1 is that the elution treatment temperature and the adsorption temperature are different, and the other settings are the same.
[0065] (1) Take 4.888g LiC2H3O2·2H2O and 18.5ml C 16 H 36 O4Ti was dissolved in 30ml and 93ml of anhydrous ethanol, respectively, to prepare two solutions A and B. A was slowly dripped into solution B and stirred continuously at room temperature for 12h to obtain a uniform mixed solution C. 2.615g of citric acid was dissolved in 30ml of ethanol solution to prepare solution D. Solution D was slowly dripped into mixed solution C, stirred continuously at room temperature for 0.5h, and then placed in an 80℃ forced air oven to dry for 48h. After drying, it was taken out and fully ground and placed in a crucible, and calcined in a muffle furnace at 330℃ / 4h. After calcination, it was taken out and fully ground and placed in a porcelain boat, and calcined in a tube furnace at 850℃ / 12h under N2 atmosphere. After calcination, it was taken out and fully ground to obtain a black adsorbent powder Li4Ti5O 12 Its XRD shows Figure 1 ,Depend on Figure 1 It can be seen that the structure of the obtained precursor is similar to that of spinel-type Li4Ti5O 12 Standard cards are consistent.
[0066] (2) The above lithium ion sieve precursor Li4Ti5O 12 The spinel titanium adsorbent H4Ti5O was obtained by acid washing with 0.15 mol / L HCl at 25 °C for 72 h, with a titanium dissolution loss of 0.31%. The spinel titanium adsorbent H4Ti5O was obtained by washing with deionized water. 12 0.25g of adsorbent was placed in 50ml of 600mg / L LiOH solution at 25℃ for 72h. The adsorption data curve is as follows: Figure 3 As shown, the adsorption capacity is about 9.13 mg / L. Figure 3 Compared with Example 1, it can be seen that the elution and adsorption temperature of 25°C / 72h will reduce the adsorption capacity of the adsorbent and increase the dissolution rate of titanium.
[0067] In summary, the present invention provides a method for preparing a titanium-based lithium ion sieve adsorbent with high adsorption performance. The preparation method of the present invention has the characteristics of simple process, low cost, and green environmental protection. In the preparation process of this method, a titanium-based lithium ion sieve adsorbent with high crystallinity, small and uniform particles can be obtained. By using a lithium source to react with a titanium compound, introducing a carbon-containing complexing agent in the reaction, and optimizing the conditions of the roasting and elution treatments, the dissolution rate of titanium can be reduced, the adsorption surface area can be expanded, thereby increasing the adsorption sites, improving the adsorption capacity, enhancing the cycle stability and adsorption rate, and shortening the adsorption equilibrium time. It has high practical value in the field of lithium extraction technology adsorption method of typical complex multi-ion interactive systems represented by salt lake brine.
[0068] The above is only a specific implementation method of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. A method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance, characterized in that: The preparation method comprises: S1. Mixing a lithium source and a titanium compound with anhydrous ethanol respectively to obtain a solution A and a solution B; S2, slowly dripping A into solution B and stirring to obtain a mixed solution C; S3, dissolving the carbon-containing complexing agent in anhydrous ethanol to obtain a solution D; S4, dropping the mixed solution D into the solution C, drying, and then calcining to obtain a lithium ion sieve precursor; S5. The lithium ion sieve precursor is subjected to elution treatment to obtain a titanium-based lithium ion sieve adsorbent with high adsorption performance.
2. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The calcination treatment comprises: calcination at 300° C. to 350° C. for 3.5 h to 4.5 h in an air atmosphere, and then calcination at 780° C. to 850° C. for 11 h to 13 h in a N2 atmosphere.
3. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 2, characterized in that: The calcination treatment includes: calcination at 330° C. for 4 hours in an air atmosphere, and then calcination at 800° C. for 12 hours in a N2 atmosphere.
4. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: In the step S1, the molar ratio of the lithium source to the titanium compound is 4-4.5:5; in the step S3, the molar ratio of the carbon-containing complexing agent to the titanium compound is 1-1.5:
5.
5. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The lithium source is selected from one or more of anhydrous or hydrated lithium acetate, anhydrous or hydrated lithium carbonate, anhydrous or hydrated lithium nitrate, anhydrous or hydrated lithium hydroxide, anhydrous or hydrated lithium sulfate, and anhydrous or hydrated lithium chloride.
6. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The elution treatment is acid washing at 20°C to 75°C for 45h to 75h.
7. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The lithium ion sieve precursor is Li4Ti5O 12 Precursor.
8. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The carbon-containing complexing agent is selected from one of citric acid, malic acid, tartaric acid and oxalic acid.
9. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The high adsorption performance titanium series lithium ion sieve type adsorbent is H4Ti5O 12 Adsorbent.
10. The method for preparing a titanium-based lithium ion sieve-type adsorbent with high adsorption performance according to claim 1, characterized in that: The temperature of the high adsorption performance titanium-based lithium ion sieve-type adsorbent when adsorbing the lithium-containing solution is controlled at 20° C. to 75° C.
Citation Information
Cited By
High-hydrophilicity titanium-based lithium ion sieve based on synergistic surface and lattice regulation and preparation method of high-hydrophilicity titanium-based lithium ion sieve
CN120841565A